Mass screening and treatment (MSaT) for identifying and treating asymptomatic cases of malaria-malaria elimination demonstration project (MEDP), Mandla, Madhya Pradesh - Akansha Singh; Harsh Rajvanshi; Mrigendra P. Singh; Sneha Bhandari; Sekh Nisar; Rajan Poriya; Vinay Telasey; Himanshu Jayswar; Ashok K. Mishra; Aparup Das; Harpreet Kaur; Altaf A. Lal; et al. (Malaria Journal, 2022)
Abstract Background Mass screening and treatment (MSaT) aims at reducing the spread of malaria in communities by identifying and treating infected persons regardless of the symptoms. This study was conducted to identify and treat asymptomatic cases using MSaT approaches in the community. Methods Three rounds of MSaT using cluster combination approaches were carried out during September 2018 to December 2019 to identify and treat asymptomatic malaria cases in the community. All individuals who were present in the household were screened using RDT irrespective of malaria related symptoms. Simultaneously thick and thin blood smear and blood spot were collected for further analysis using microscopy and diagnostic PCR done in a subset of the samples. Results Logistic regression analysis revealed that asymptomatic malaria cases significantly less among the older age groups compared with < 5 years children (OR ranged between 0.52 and 0.61; p < 0.05), lowest in cluster 4 (OR = 0.01; p < 0.0001); during third round of MSaT survey (OR = 0.11; p < 0.0001) and significantly higher in moderate to high endemic areas (OR = 88.30; p < 0.0001). Conclusion Over the three rounds of MSaT, the number of asymptomatic cases were significantly less in the older age groups, and during third round. Similarly, the asymptomatic cases were significantly less in the low endemic area with API < 1 (cluster four). Therefore, the malaria elimination programme may consider the MSaT strategy to identify asymptomatic cases that would be otherwise missed by routine fever based surveillance. This MSaT strategy would help accomplish the malaria elimination goal in an expedited manner.